Super-Resolution DoA Estimation on a Co-Prime Array via Positive Atomic Norm Minimization - Hyeonjin Chung (Energies, 2020)
A super-resolution direction-of-arrival (DoA) estimation algorithm that employs a co-prime array and positive atomic norm minimization (ANM) is proposed. To exploit larger array cardinality, the co-prime array vector is constructed by arranging elements of a correlation matrix. The positive ANM is a technique that can enhance resolution when the coefficients of the atoms are the positive real numbers. A novel optimization problem is proposed to ensure the coefficients of the atoms are the positive real numbers, and the positive ANM is employed after solving the optimization problem. The simulation results show that the proposed algorithm achieves high resolution and has lower complexity than the other ANM-based super-resolution DoA estimation algorithm.